Maurice Pialat's À nos amours = To our loves - Langmann, Arlette 1946-; Loiseleux, Jacques; Cloquet, Julien; Bonnaire, Sandrine 1967-; Ker, Evelyne; Besnehard, Dominique; Collard, Cyril 1957-1993; Odent, Christophe (<<The>> Criterion Collection, 2006)
A fifteen-year-old Parisian girl embarks on a sexual rampage in an effort to separate herself from her overbearing father, ineffectual mother, and brutish brother.
Bildformat 1.66:1 aspect ratio. - New, restored high-definition digital transfer
Orig.: Frankreich 1983
Enth. "The human eye", a 1999 documentary on the film ; archival interview with Maurice Pialat on the set ; a 2003 interview with Sandrine Bonnaire ; new interviews with filmmakers Catherine Breillat and Jean-Pierre Gorin ; actor auditions
Keywords: Dysfunctional families -- Drama; Melodrama; Promiscuity -- Drama; Teenage girls -- Drama; Feature films; Fiction films; Melodrama - Feature